2017
DOI: 10.1038/s41598-017-14043-2
|View full text |Cite
|
Sign up to set email alerts
|

Health impact of E-cigarettes: a prospective 3.5-year study of regular daily users who have never smoked

Abstract: Although electronic cigarettes (ECs) are a much less harmful alternative to tobacco cigarettes, there is concern as to whether long-term ECs use may cause risks to human health. We report health outcomes (blood pressure, heart rate, body weight, lung function, respiratory symptoms, exhaled breath nitric oxide [eNO], exhaled carbon monoxide [eCO], and high-resolution computed tomography [HRCT] of the lungs) from a prospective 3.5-year observational study of a cohort of nine daily EC users (mean age 29.7 (±6.1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 46 publications
2
85
0
1
Order By: Relevance
“…Long-term EC usage had a threshold of ≥2 years, in accordance with recent prospective studies 15,16 . A current smoker was defined as an adult who smoked 100 cigarettes in his lifetime and who currently smokes conventional cigarettes 24 .…”
Section: Baseline Definitionssupporting
confidence: 85%
See 1 more Smart Citation
“…Long-term EC usage had a threshold of ≥2 years, in accordance with recent prospective studies 15,16 . A current smoker was defined as an adult who smoked 100 cigarettes in his lifetime and who currently smokes conventional cigarettes 24 .…”
Section: Baseline Definitionssupporting
confidence: 85%
“…Another recent investigation, a 2-year longitudinal follow-up study in the US, found significantly higher tobacco quit attempts and cessation rates among EC users 15 . A prospective 3.5year observational study among a cohort of 9 never smokers who used ECs daily found no significant harmful health effects from EC use 16 . This study was, however, limited by its relatively small sample size.…”
Section: Introductionmentioning
confidence: 98%
“…In young, normotensive nonsmokers, Fogt et al (48) found that e-cig inhalation preferentially increased both resting and exercise diastolic BP 40 min following nicotine inhalation. A recent prospective 3.5-yr observational study by Polosa et al (112) found that in a population of healthy e-cig users who had never smoked conventional cigarettes, there was no change in systolic or diastolic BP compared with healthy never smokers and non-e-cig users. The authors thus concluded that daily e-cig use is not associated with adverse health concerns.…”
Section: Nicotine and The Ras In Cardiovascular Dysfunctionmentioning
confidence: 97%
“…Nitric oxide is involved in antimicrobial activity against lung pathogens and has anti‐tumour effects, whereas eCO is a biomarker of smoking that reflects airway inflammation; thus, normalization of FeNO and eCO might support the use of E‐cigarettes to reverse the harmful effects of CS in the lungs. A prospective 3.5‐year observational study of nine E‐cigarette users who never smoked conventional cigarettes found E‐cigarette use did not alter healthy outcome including blood pressure, heart rate, body‐weight, lung function, respiratory symptoms, exhaled breath nitric oxide (eNO), exhaled carbon monoxide (eCO) or high‐resolution computed tomography of the lungs …”
Section: Effects Of E‐cigarettes In Humansmentioning
confidence: 99%
“…A prospective 3.5year observational study of nine E-cigarette users who never smoked conventional cigarettes found E-cigarette use did not alter healthy outcome including blood pressure, heart rate, body-weight, lung function, respiratory symptoms, exhaled breath nitric oxide (eNO), exhaled carbon monoxide (eCO) or high-resolution computed tomography of the lungs. 20 In addition to helping to reduce harmful effects in smokers with normal lung function, E-cigarette use may also benefit patients with respiratory and systemic diseases. COPD patients who switched to the use of E-cigarettes reduced their CS consumption, and more than half stopped cigarette smoking completely during a 12-month follow-up.…”
Section: Benefits Of E-cigarette Usementioning
confidence: 99%